Frequency of down syndrome: an experience of a tertiary care diagnostic laboratory in India - Pande, Shailesh; Salaskar, Vidya; Pais, Anurita; Pradhan, Gauri; Patil, Smita; Parab, Chaitali; Jadhav, Yamini; Matkar, Sunmeet (International Journal of Advances in Medicine, 2017)
Background: Down syndrome or Trisomy 21 is a genetic condition involving the presence of extra copy of chromosome 21. It is the most common chromosomal abnormality within paediatric age group. The objective of our study was to determine the frequency of Down syndrome and its various cytogenetic types in cases with clinical suspicion of Down syndrome received at the Department of Cytogenetics, Metropolis Healthcare Limited, Mumbai, India. Methods: Our study was performed on peripheral blood (2-3 ml) collected in Sodium Heparin Vacutainers obtained from 714 patients with clinical suspicion of Down syndrome. All the samples were requested for GTG staining and banding, while the cultures were set and analysed by GTG–banding at 450-550 band level. The period of our study was from January-2015 to December-2016. Results: Out of 714 samples referred, about 657 showed trisomy of chromosome 21. While, out of 657 cases, 551 (83.87%) cases were detected with free trisomy, Robertsonian translocation in 52 cases (7.91%), Mosaic pattern in 16 cases (2.44%). Our study also recorded trisomy with additional polymorphic variation in 35 cases (5.33%) and 3 cases (0.46%) with additional abnormality. Conclusions: According to the extensive literature available which states that the clinical diagnosis of Down syndrome is relatively easy, it is the pattern of chromosomal aberration that is extremely important. Identification of this pattern will assist in the estimation of the possibility of recurrence risk while counselling the parents. Overall, it will benefit the couple to arrive at an informed decision and will eventually minimize the frequency of disease in the society. Moreover, it will also assist the close blood relatives to know their risk of having baby with Down syndrome. It is to be noted that since the study was performed in a tertiary care laboratory, the percentage of cytogenetic.